KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR MENGGUNAKAN VISUALISASI POSTER SEDERHANA - Fatimah Nurul Aufa; Imaniar Purbasari; Eko Widianto (PGSD Universitas Muria Kudus, 2020)
This study aims to describe the improvement of students' speaking skills through simple poster media on the theme of my hero grade IV SDN 1 Loram Kulon Kudus. This research was conducted in class IV SDN 1 Loram Kulon with research subjects of 21 students. This research lasted for 2 cycles. Cycle 1, namely in sub-schemes 2 learning 1 and 3. Cycle 2 takes place in sub-schemes 2 in learning 4 and 6. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. This research shows that the use of poster media can improve speaking skills at SDN 1 Loram Kulon Kudus, this can be seen from the increase in cycle 1 to cycle 2 from 58% to 78% of the total 21 students.